100 Gy 60Co γ-Ray Induced Novel Mutations in Tetraploid Wheat. (19th May 2014) - Yang, Chuntao; Zhu, Jianshu; Jiang, Yun; Wang, Xiaolu; Gu, Mengxue; Wang, Yi; Kang, Houyang; Fan, Xing; Sha, Lina; Zhang, Haiqin; Xuan, Pu; Zhou, Yonghong
Abstract : 10 accessions of tetraploid wheat were radiated with 100 Gy 60 Co γ -ray. The germination energy, germination rate, special characters (secondary tillering, stalk with wax powder, and dwarf), meiotic process, and high-molecular-weight glutenin subunits (HMW-GSs) were observed. Different species has different radiation sensibility. With 1 seed germinated (5%), T. dicoccum (PI434999) is the most sensitive to this dose of radiation. With a seed germination rate of 35% and 40%, this dose also affected T. polonicum (As304) and T. carthlicum (As293). Two mutant dwarf plants, T. turgidum (As2255) 253-10 and T. polonicum (As302) 224-14, were detected. Abnormal chromosome pairings were observed in pollen mother cells of both T. dicoccoides (As835) 237-9 and T. dicoccoides (As838) 239-8 with HMW-GS 1Ax silent in seeds from them. Compared with the unirradiated seed of T. polonicum (As304) CK, a novel HMW-GS was detected in seed of T. polonicum (As304) 230-7 and its electrophoretic mobility was between 1By8 and 1Dy12 which were the HMW-GSs of Chinese Spring. These mutant materials would be resources for wheat breeding.